2010
DOI: 10.1073/pnas.1006500107
|View full text |Cite
|
Sign up to set email alerts
|

Success or failure of vaccination for HPV16-positive vulvar lesions correlates with kinetics and phenotype of induced T-cell responses

Abstract: One half of a group of 20 patients with human papillomavirus type 16 (HPV16)-induced vulvar intraepithelial neoplasia grade 3 displayed a complete regression (CR) after therapeutic vaccination with HPV16 E6/E7 synthetic long peptides. Patients with relatively larger lesions generally did not display a CR. To investigate immune correlates of treatment failure, patients were grouped according to median lesion size at study entry, and HPV16-specific immunity was analyzed at different time points by complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
218
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(228 citation statements)
references
References 34 publications
6
218
0
4
Order By: Relevance
“…In HNSCC the ratio between CD8þ and regulatory T cells is associated with disease. 5,33 Similarly, in HPV16 induced genital malignancies the presence of FoxP3 positive as well as FoxP3 negative HPV16 specific regulatory T cells in tumor and LN is described 30,36,38 and a low CD8/Treg T-cell ratio is associated with worse outcome. 39 While the regulatory function of the CD4þCD25þFoxp3þ T cells present in TILs needs to be confirmed, at least one of our isolated clones clearly exerted regulatory function.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In HNSCC the ratio between CD8þ and regulatory T cells is associated with disease. 5,33 Similarly, in HPV16 induced genital malignancies the presence of FoxP3 positive as well as FoxP3 negative HPV16 specific regulatory T cells in tumor and LN is described 30,36,38 and a low CD8/Treg T-cell ratio is associated with worse outcome. 39 While the regulatory function of the CD4þCD25þFoxp3þ T cells present in TILs needs to be confirmed, at least one of our isolated clones clearly exerted regulatory function.…”
Section: Discussionmentioning
confidence: 98%
“…In TIL we find different subsets of HPV16-specific T cells (Th1, Th2, CTL and Tregs) with different cytokine profiles (IL-2, IFNc, IL-5) comparable to what is found in anogenital HPV16 induced lesions. 29,35,36 Together this advocates that local adaptive immune cells might play a role in the response to therapy and the altered survival of this patient group.…”
Section: Discussionmentioning
confidence: 98%
“…In human, the group of Peter Van der Bruggen has demonstrated that the CD4 + T-cell response of melanoma patients to a MAGE-A3-derived peptide vaccine involves regulatory T cells [88]. In individuals vaccinated with E6/E7-derived long peptides, immunosuppressive cells has been shown to expand [89], correlating to the development of resistance against an anti-HPV therapeutic vaccine [90]. A better identification of the specificity of Tregs in cancer patients will help to design TAAbased vaccine that induce optimal Teff responses while failing to activate Tregs to significant extents.…”
Section: Specificity Of Tregsmentioning
confidence: 99%
“…The importance of a robust effector T-cell response in mediating successful outcomes to immunotherapy has been recently shown in a clinical human papillomavirus vaccine trial for pre-malignant vulval intraepithelial neoplasia, in which measured T-cell responses strongly correlated with regression of lesions (Kenter et al, 2009;Welters et al, 2010; Figure 2). However, in other clinical trials of tumour vaccines against larger, invasive malignancies the effective generation of tumour antigenspecific T cells in peripheral blood has not predicted clinical efficacy Gajewski et al, 2006).…”
Section: Why Does An Anti-tumour T-cell Response Still Fail To Eradicmentioning
confidence: 93%